2007
DOI: 10.1021/bi700493m
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical Interactions in the Management of RNA Structural Blocks by the Transcription Termination Rho Helicase

Abstract: To trigger transcription termination, the ring-shaped RNA-DNA helicase Rho from Escherichia coli chases the RNA polymerase along the nascent transcript, starting from a single-stranded C-rich Rut (Rho utilization) loading site. In some instances, a small hairpin structure divides harmlessly the C-rich loading region into two smaller Rut subsites, best exemplified by the tR1 terminator from phage lambda. Here, we show that the Rho helicase can also elude a RNA structural block located far downstream from the si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 48 publications
2
43
0
Order By: Relevance
“…It is well established that the sequence of the RNA itself has a pronounced impact on whether a transcript will be acted upon by Rho (12,[27][28][29]. Binding of pyrimidine-rich sequences to the N-terminal RNA-binding domains of Rho is a particularly well-known accelerant of Rho's ATPase activity (30), with presteady-state ATPase assays showing that the formation of a catalytically competent Rho ring is governed by a rate-limiting RNA-and ATP-dependent conformational change (8).…”
mentioning
confidence: 99%
“…It is well established that the sequence of the RNA itself has a pronounced impact on whether a transcript will be acted upon by Rho (12,[27][28][29]. Binding of pyrimidine-rich sequences to the N-terminal RNA-binding domains of Rho is a particularly well-known accelerant of Rho's ATPase activity (30), with presteady-state ATPase assays showing that the formation of a catalytically competent Rho ring is governed by a rate-limiting RNA-and ATP-dependent conformational change (8).…”
mentioning
confidence: 99%
“…The mechanism by which Rho induces transcription termination involves a primary interaction of the protein with a naked portion of the nascent transcript, followed by ATPdriven translocation and the disruption of the transcription elongation complex at downstream sites. Previous in vitro and in vivo studies in our laboratory have shown that a well-defined Rho-dependent terminator is not an absolute prerequisite for Rho activity; any RNA sequence with adequately spaced C residues or certain RNA structures such as hairpins can serve as efficient loading sites for Rho (18,58). Also, Rho is able to compete with other proteins for binding to a transcript, a process used in prokaryotic gene regulation (66).…”
mentioning
confidence: 99%
“…6A and B). 23 This phenomenon is most likely due to the accommodation of the intervening RNA structure on the PBS face of the Rho ring (Fig. 6A) during the early activation steps (Fig.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 98%
“…18 Suitable helicase substrates for the two enzymes contain a 'tracking' RNA strand with a single-stranded region upstream from the duplex region. 16,18 For ec Rho, helicase activity is optimal if the single-stranded region is more than ~70 nt-long and contains a natural 16,17,[20][21][22]34 or synthetic 18,19,23 cytosine-rich Rut (Rho Utilization) loading site. A long (>100 nt) single-stranded region also appears necessary for ϕ8 P4 helicase activity (our unpublished observations).…”
Section: Substrate Selectivity and Utilization By P4 And Rho Enzymesmentioning
confidence: 99%
See 1 more Smart Citation